A new class of hybrid AC/AC direct power converters - Klumpner, Christian; Wijekoon, Thiwanka; Wheeler, Patrick (2005)
Variable voltage and variable frequency conversion of electrical energy from an AC source to an AC load is done in traditional power converters via a DC-link where an energy storage element (electrolytic capacitors) is situated. Despite its well-known benefits, it has the disadvantage of being bulky and to limit the converter lifetime. On the other hand, Direct Power Conversion (DPC) is an attractive concept, which doesn’t need an energy storage buffer, but has two main disadvantages: reduced voltage transfer ratio (<0.86) and low immunity to voltage supply disturbances. This paper proposes a new approach to perform the power conversion by mixing various standard topologies of well-known power converters in order to improve their performance/behavior. Simulation and experimental results prove that the hybrid structures are able to boost the output voltage capability (some above unity) and/or to fully compensate unbalanced voltage supply.